2008
DOI: 10.1038/pcan.2008.18
|View full text |Cite
|
Sign up to set email alerts
|

Race and prostate weight as independent predictors for biochemical recurrence after radical prostatectomy

Abstract: We hypothesized that factors beyond pathological stage, grade, PSA and margin status would be important predictors of biochemical recurrence (BCR) after radical prostatectomy (RP). A cohort of 3194 patients who underwent RP between 1988 and 2007 and who had neither neoadjuvant therapy nor postoperative adjuvant hormonal therapy was retrieved from the Duke Prostate Center database. Age, prostate-specific antigen (PSA), pathological Gleason score (pG), lymph node status, seminal vesicle invasion (SVI), extracaps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 32 publications
4
48
0
1
Order By: Relevance
“…This index provides the percentage of correct predictions by the model with values of 0.5 equaling the flip of a coin and 1.0 representing all patients predicted correctly. Predictive accuracy of the following nine models was assessed: a basic clinical model (based on clinical stage, biopsy Gleason score, and logtransformed preoperative PSA) developed in this patient cohort, a basic pathological model (based on pathological stage, prostatectomy Gleason sum, and log-transformed preoperative PSA) developed in this patient cohort, the D'Amico risk classification [3], Kattan's preoperative [4] and postoperative [5] nomograms, a nomogram developed by our team based on a separate patient cohort from the Duke Prostate Center database [6], the CAPRA model [7], which has been previously validated in the SEARCH cohort for predicting BCR [17], a model from the Center for Prostate Disease Research (CPDR) [8], and a model from Johns Hopkins Hospital (JHH) [9]. Thus, none of the previously published models were developed based on data from the SEARCH database.…”
Section: Discussionmentioning
confidence: 99%
“…This index provides the percentage of correct predictions by the model with values of 0.5 equaling the flip of a coin and 1.0 representing all patients predicted correctly. Predictive accuracy of the following nine models was assessed: a basic clinical model (based on clinical stage, biopsy Gleason score, and logtransformed preoperative PSA) developed in this patient cohort, a basic pathological model (based on pathological stage, prostatectomy Gleason sum, and log-transformed preoperative PSA) developed in this patient cohort, the D'Amico risk classification [3], Kattan's preoperative [4] and postoperative [5] nomograms, a nomogram developed by our team based on a separate patient cohort from the Duke Prostate Center database [6], the CAPRA model [7], which has been previously validated in the SEARCH cohort for predicting BCR [17], a model from the Center for Prostate Disease Research (CPDR) [8], and a model from Johns Hopkins Hospital (JHH) [9]. Thus, none of the previously published models were developed based on data from the SEARCH database.…”
Section: Discussionmentioning
confidence: 99%
“…This result conflicts with prior studies, which concluded that there was an inverse correlation between prostate weight and more-advanced disease. [33][34][35] However, none of the reviewed studies analyzed prostate weight in respect to LN status, and we find our observation novel.…”
Section: Commentmentioning
confidence: 96%
“…The size of a normal prostate is 20-30 cc 25,26 and reported medians in the literature set the median for diseased prostate volume around 35-45 cc. 2,12,13,15,24 In our study the median prostate volume was 38.4 cc, with only 25% of men having prostates larger than 50 cc and 10% larger than 64 cc. As a result, our finding that men with prostate volumes less than 35 cc have a 25% increased risk for PSAR compared to men with larger volume prostates provides clinicians with a clinically relevant value by which to assess patients risk for PSAR following RP.…”
Section: Pvmentioning
confidence: 46%
“…Previous studies from this team and others showed that men with small PV had higher risk of PSAR. 2,12,14,15 The reason for this remains unknown, however a number of potential explanations exist. It has been suggested that men with smaller prostates may have lower levels of testosterone which has been shown to correlate with more aggressive prostate cancer 22 .…”
Section: Pvmentioning
confidence: 99%
See 1 more Smart Citation